2020
DOI: 10.1186/s12885-020-07320-3
|View full text |Cite
|
Sign up to set email alerts
|

Post-diagnostic antipsychotic use and cancer mortality: a population based cohort study

Abstract: Background: Many antipsychotics elevate prolactin, a hormone implicated in breast cancer aetiology however no studies have investigated antipsychotic use in patients with breast cancer. This study investigated if antipsychotic use is associated with an increased risk of cancer-specific mortality among breast cancer patients. Methods: A cohort of 23,695 women newly diagnosed with a primary breast cancer between 1st January 1998 and 31st December 2012 was identified from the UK Clinical Practice Research Datalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Mentally ill patients face disparities in screening/prevention of common cancers and are more likely to die from breast cancer, and women with psychotic disorders are about half as likely as the general population to receive mammography screening 35 . Our data and the other publications 36–43 reviewed previously suggest that the use of antipsychotic drugs that elevate prolactin may contribute to incident cases of breast cancer. We also report a surprisingly elevated association of breast cancer risk with category 2 drugs, particularly in younger women, aged 18 to 50 years.…”
Section: Discussionmentioning
confidence: 55%
“…Mentally ill patients face disparities in screening/prevention of common cancers and are more likely to die from breast cancer, and women with psychotic disorders are about half as likely as the general population to receive mammography screening 35 . Our data and the other publications 36–43 reviewed previously suggest that the use of antipsychotic drugs that elevate prolactin may contribute to incident cases of breast cancer. We also report a surprisingly elevated association of breast cancer risk with category 2 drugs, particularly in younger women, aged 18 to 50 years.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, we examined all-cause mortality in the available studies. Data from the study by Hicks ( 30 ) suggested higher all-cause mortality in patients with cancer who were exposed to antipsychotics (OR, 1.54; 95% CI, 1.29–1.82). A summary of our findings is provided in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous observational studies have been conducted examining the relationship between antipsychotic use and breast cancer outcomes. In a dozen such studies that were reviewed, findings were mixed (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Many studies found no evidence of association between exposure to prolactin increasing antipsychotics and breast cancer, while others, reported positive associations, including recent publications by Taipale et al and Rahman et al (10,11).…”
Section: Introductionmentioning
confidence: 99%